The dynamic relationship between government debt, fiscal consolidation, and economic growth in South Africa: A threshold analysis - Eugene Msizi Buthelezi; Phocenah Nyatanga (Cogent Economics & Finance, 2023)
This paper investigates the threshold impact of government debt on economic growth in the presence of fiscal consolidation in South Africa from 1979 to 2022. The autoregressive threshold regime (TAR) model and two-stage least squares (2SLS) are used. The contribution of the paper is on the estimation of the threshold of government debt using the first difference, dummy variables, and the TAR in the presence of fiscal consolidation in South Africa. The TAR provides evidence with the consideration of fiscal consolidation, there is evidence of the U-shape impact of domestic government debt on gross domestic product per person. At a high threshold, there is evidence of an S-shape impact on gross domestic product per person when there is a range threshold. Overall high domestic government debt harms gross product per person and results in fiscal consolidation not being able to stimulate gross domestic product per person. It is recommended for fiscal authorities to not use fiscal consolidation when the domestic government debt is above 60% in South Africa.
Keywords: E62; F20; F21; F30; F34; O40; 330; cyclically adjusted primary balance (CAPB); domestic government debt; fiscal consolidation